New HPLC method for determination of fluvastatin anti-hyperlipidemic drug in bulk and pharmaceutical dosage using simvastatin as internal standard - Ashour, Safwan; Khateeb, Mouhammed (Drug Analytical Research, 2026)
A new, and reliable RP–HPLC method has been investigated and validated for the assay of fluvastatin sodium (FVS) in pharmaceutical capsules. The chromatographic method was carried out using an ODS Hypersil C18 column (250×4.6 mm i.d., 5 µm particle size); a mixture containing methanol and 0.10 M ammonium acetate (70:30, v/v), a flow rate 1.0 mL/min and UV detection at 305 nm. The retention time for fluvastatin and the internal standard simvastatin (SVS) was found to be 3.2 and 6.4 minutes, respectively. Despite the wide range of the analyte concentration, the method showed good linearity (r>0.9998) in the range 2.0–320.0 µg mL-1. The proposed method was validated with respect to linearity, accuracy, precision, and robustness. The limit of detection was 0.54 µg mL-1. The successful application of the new HPLC method indicates its routine use to quantify of FVS in pharmaceuticals.